2020
DOI: 10.1002/fsn3.1669
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive monitoring storage quality of apples at different temperatures by near‐infrared transmittance spectroscopy

Abstract: Apple is the most widely planted fruit in the world and is popular in consumers because of its rich nutritional value. In this study, the portable near‐infrared (NIR) transmittance spectroscopy coupled with temperature compensation and chemometric algorithms was applied to detect the storage quality of apples. The postharvest quality of apples including soluble solids content (SSC), vitamin C (VC), titratable acid (TA), and firmness was evaluated, and the portable spectrometer was used to obtain near‐infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…also showed that CARS extracted fewer feature bands than UVE-SPA, but also lost more useful bands, resulting in a worse subsequent regression effect. This was consistent with the findings of Guo et al ( Guo et al., 2020 ). They compared the results of the UVE-SPA-PLS and CARS-SPA-PLS models with those of the UVE-PLS and CARS-PLS models, and found that the predictive performance of the SPA engagement model was slightly lower than that of UVE-PLS and CARS-PLS.…”
Section: Resultssupporting
confidence: 94%
“…also showed that CARS extracted fewer feature bands than UVE-SPA, but also lost more useful bands, resulting in a worse subsequent regression effect. This was consistent with the findings of Guo et al ( Guo et al., 2020 ). They compared the results of the UVE-SPA-PLS and CARS-SPA-PLS models with those of the UVE-PLS and CARS-PLS models, and found that the predictive performance of the SPA engagement model was slightly lower than that of UVE-PLS and CARS-PLS.…”
Section: Resultssupporting
confidence: 94%
“…Noteworthily, attention is given to increasing the universality of the models taking into account varying conditions of the measurement. For instance, Guo et al recently compared the effects of temperature on the models and used preprocessing methods and variable selection methods to improve the prediction performance under varying conditions [334]. The results showed that the NIR system could accurately predict the quality attributes of apples stored for different periods, with promising results for firmness, SSC, titratable acidity, and vitamin C. Noteworthily, attention is given to increasing the universality of the models taking into account varying conditions of the measurement.…”
Section: Optimization Of Storage Conditionsmentioning
confidence: 99%
“…The results showed that the NIR system could accurately predict the quality attributes of apples stored for different periods, with promising results for firmness, SSC, titratable acidity, and vitamin C. Noteworthily, attention is given to increasing the universality of the models taking into account varying conditions of the measurement. For instance, Guo et al recently compared the effects of temperature on the models and used preprocessing methods and variable selection methods to improve the prediction performance under varying conditions [334]. The results showed that the NIR system could accurately predict the quality attributes of apples stored for different periods, with promising results for firmness, SSC, titratable acidity, and vitamin C.…”
Section: Optimization Of Storage Conditionsmentioning
confidence: 99%
“…Near infrared (NIR) spectroscopy has gained remarkable value as a non-destructive analytical technique and it has become the tool of choice in several fields of application [1]. Because of the advantages of the capacity for quickmeas [2], nondestructive [3] and capable of on-site analysis [4,5], the portable spectrometers are extensively used determining and quantitative analysis of chemical components of various samples in the outdoor environment [6][7][8][9]. However, compared with laboratory conditions, the outdoor working environment of the portable instruments is more complicated [10].…”
Section: Introductionmentioning
confidence: 99%